Potensi dan Daya Tarik Wisata Kecamatan Medan Tuntungan dalam Perspektif Arsitektur Pariwisata - Adithya Prasetyo; Puttu Dwi Syahputra; Dara Wisdianti (Jurnal Teknik dan Teknologi Indonesia, 2023)
Medan Tuntungan Sub-district is one of the strategic areas in Medan City that has great potential in the development of the tourism sector. This research aims to identify and analyze the characteristics of tourism architecture and the attractiveness of tourist destinations in the area. The method used is descriptive qualitative with data collection techniques through literature study and observation of several leading tourist attractions, including Kenanga Garden, Royal Sumatra Golf Course, Rajasyah Outbound & Edu Center, and Graha Maria Annai Velangkanni. The results showed that each destination has its own charm in terms of attractions, accessibility, amenities, and ancillary facilities. The existence of adequate facilities and a natural atmosphere are the added value of these destinations. However, some locations still need improvement in terms of infrastructure and promotion. Therefore, collaboration between the government, tourism managers, and the community is needed to support the development of sustainable tourism in Medan Tuntungan Sub-district.